Development of Differentiated Mathematics E-books Based on Langkat Malay Culture to Improve Students' Functional Thinking and Critical Thinking Skills - Marhamah Hasibuan, Ainul; Fauzi; Ermawati (Journal of Practice Learning and Educational Development, 2025)
This study aims to develop a differentiated mathematics e-book based on Langkat Malay culture that is feasible, effective, and practical in improving the functional thinking and critical thinking abilities of junior high school students. The research method used is Research and Development (R&D) with the 4-D Thiagarajan model which includes the stages of define, design, develop, and disseminate. The research subjects were students of Private Junior High School PAB 13 Langkat, with data obtained through functional thinking and critical thinking tests, expert validation questionnaires, and teacher and student response questionnaires. The results of the study showed that from the aspect of feasibility, validation by material, language, and design experts obtained an average percentage of 88.6% which is included in the very feasible category. From the aspect of effectiveness, the use of e-books is proven to improve functional thinking abilities with an average N-Gain of 0.70 and critical thinking abilities with an average N-Gain of 0.72, both of which are included in the effective category. In terms of practicality, teachers responded 89.3% and students 87.9%, with an average of 88.6%, which is considered very practical. Therefore, the differentiated mathematics e-book based on Langkat Malay culture can be used as an alternative innovative teaching material that is not only in line with the curriculum but also culturally relevant, and able to improve students' higher-order thinking skills. This product has the potential to contribute to enriching mathematics learning resources that are contextual, interactive, and support 21st-century learning.